We want what's ours : learning from South Africa's land restitution program - Atuahene, Bernadette (Oxford University Press, 2014)
Millions of people all over the world have been displaced from their homes and property. Dispossessed individuals and communities often lose more than the physical structures they live in and their material belongings, they are also denied their dignity. These are dignity takings, and land dispossessions occurring in South Africa during colonialism and apartheid are quintessential examples. There have been numerous examples of dignity takings throughout the world, but South Africastands apart because of its unique remedial efforts. The nation has attempted to move beyond the more common step o.